De novo tandem duplication 17p11→cen. Issue 2 (April 1983) - Docherty, Z; Hultén, M A; Honeyman, M M
Abstract : A dicentric chromosome 17 is described in a 5-year-old girl with minor malformations and severe mental retardation. The anomaly is interpreted as a de novo duplication of band 17p11 and centromere 17.